Crocetin Enhances Temozolomide Efficacy in Glioblastoma Therapy Through Multiple Pathway Suppression - Tsai, Wei-En; Liu, Yen-Tsen; Kuo, Fu-Hsuan; Cheng, Wen-Yu; Shen, Chiung-Chyi; Chiao, Ming-Tsang; Huang, Yu-Fen; Liang, Yea-Jiuen; Yang, Yi-Chin; Hsieh, Wan-Yu; Chen, Jun-Peng; Liu, Szu-Yuan; et al. (Current neurovascular research, 2024)
Glioblastoma multiforme (GBM) is an aggressive type of brain tumor that is difficult to remove surgically. Research suggests that substances from saffron, namely crocetin and crocin, could be effective natural treatments, showing abilities to kill cancer cells. Our study focused on evaluating the effects of crocetin on glioma using the U87 cell line. We specifically investigated how crocetin affects the survival, growth, and spread of glioma cells, exploring its impact at concentrations ranging from 75-150 μM. The study also included experiments combining crocetin with the chemotherapy drug Temozolomide (TMZ) to assess potential synergistic effects. Crocetin significantly reduced the viability, proliferation, and migration of glioma cells. It achieved these effects by decreasing the levels of Matrix Metallopeptidase 9 (MMP-9) and Ras homolog family member A (RhoA), proteins that are critical for cancer progression. Additionally, crocetin inhibited the formation of cellular structures necessary for tumor growth. It blocked multiple points of the Ak Strain Transforming (AKT) signaling pathway, which is vital for cancer cell survival. This treatment led to increased cell death and disrupted the cell cycle in the glioma cells. When used in combination with TMZ, crocetin not only enhanced the reduction of cancer cell growth but also promoted cell death and reduced cell replication. This combination therapy further decreased levels of high mobility group box 1 (HMGB1) and Receptor for Advanced Glycation End-products (RAGE), proteins linked to inflammation and tumor progression. It selectively inhibited certain pathways involved in the cellular stress response without affecting others. Our results underscore the potential of crocetin as a treatment for glioma. It targets various mechanisms involved in tumor growth and spread, offering multiple avenues for therapy. Further studies are essential to fully understand and utilize crocetin's benefits in treating glioma.